Epidemiological study of migraine in the state of São Paulo between 2019-2023 and the interference of oral contraceptives - Caetano, Maria Clara Calixto; Brandão , Brenda Lopes; Boreggio, Hugo Berdejo; Silva, Júlia Esteca da; Schuch, Karolina Lemos; Stetter, Letícia Loreta Roque; Oliveira , Lorena Pedro de; Mota, Nicolas França; Silva, Celijane Almeida (Headache Medicine, 2024)
Introduction: Migraine, a chronic neurovascular disease, manifests as a primary headache disorder with varying degrees of severity. Duringmenstruation, a rapid decrease in estrogen levels often triggers migraineattacks without aura, affecting approximately 50-60% of women. Conversely, high estrogen levels can lead to migraine attacks with aura. Women with a history of migraine with aura are advised not to use combined oral contraceptives (COCs) due to the increased risk of stroke and thromboembolicevents. Additionally, those who develop migraines while on medication are recommended to discontinue its use. Objectives: This study aims to analyzethe epidemiological patterns of migraine-related hospitalizations in the state ofSão Paulo and investigate the influence of oral contraceptives in patients with a prior history of migraine. Methodology: Conducted as an ecological, retrospective, and descriptive study from DATASUS regarding the epidemiologyof migraine in the state of São Paulo from 2019 to 2023, focusing on variablessuch as hospitalizations, age groups, race/ethnicity, and year of treatment. Articles from the past 10 years in english and portuguese were selected, and a comprehensive literature review on the interference of oral contraceptive use was conducted using the databases PubMed, Scielo, and Electronic JournalCollection Health. Results: There were a total of 9,316 hospitalizations due tomigraine in the state of São Paulo between 2019-2023, with a total of 2,101 in 2023, and the lowest rate in 2021, with 1,517 hospitalizations. There was a predominance of females and white individuals, corresponding to 68.9% (N=6,424) and 58.7% (N=5,476) of cases, respectively. Additionally, researchfound that around 70% of women in Brazil use some form of contraceptivemethod, with 23% corresponding to COCs and female sterilization. Conclusion: The epidemiological profile highlighted a higher prevalenceamong women and white individuals. The use of combined oral contraceptivesemerged as a contributing factor to the occurrence of migraines in women, attributed to estrogen-induced vasoconstriction triggering migraine attacks. Consequently, women with this medical history face a risk of stroke, necessitating careful consideration of contraceptive options.